2021
DOI: 10.1097/md.0000000000025725
|View full text |Cite
|
Sign up to set email alerts
|

Indonesian registry on atrial fibrillation (OneAF)

Abstract: Background: Data on the optimal therapeutic international normalized ratio (INR) for non-valvular and valvular atrial fibrillation (AF) in Indonesia is currently unavailable. Therefore, we designed the Indonesian Registry on Atrial Fibrillation (OneAF) registry in order to seek a safe and beneficial range of INR in Indonesian patients with non-valvular and valvular AF. Methods/design: The OneAF registry is a nationwide collaboration of the Indonesian Heart Rhythm Societ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Anat et al 14 reported that AF detection reached 6% at age ≥50 years with CHA₂DS₂‐VASc values >1. This study was also conducted on patients aged 50–75 years because according to OneAF registry data, it is said that the average age of AF patients in Indonesia is 57.52 (50.6 ± 78.2) years 15 …”
Section: Discussionmentioning
confidence: 99%
“…Anat et al 14 reported that AF detection reached 6% at age ≥50 years with CHA₂DS₂‐VASc values >1. This study was also conducted on patients aged 50–75 years because according to OneAF registry data, it is said that the average age of AF patients in Indonesia is 57.52 (50.6 ± 78.2) years 15 …”
Section: Discussionmentioning
confidence: 99%
“…However, data from a national registry showed that in Indonesia patients are younger, with the majority between 41 and 60 years old (Figure 4), and permanent AF is common (31%) (Figure 5). 19 AF distribution varies depending on ethnicity. Based on risk factors, the reported prevalence of AF is lower than expected, suggesting the possibility of underidentification.…”
Section: Individual Country Reportsmentioning
confidence: 99%
“…When anticoagulation is prescribed, warfarin is used because direct oral anticoagulants are not covered by national health insurance. However, the time in therapeutic range with warfarin treatment is only 37% 19,20 . The availability of test facilities that can measure the international normalized ratio (INR) is limited and not well distributed in Indonesia, which has led to the reluctance of primary care physicians to prescribe warfarin.…”
Section: Individual Country Reportsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the time in therapeutic range with warfarin treatment is only 37%. 19 , 20 The availability of test facilities that can measure the international normalized ratio (INR) is limited and not well distributed in Indonesia, which has led to the reluctance of primary care physicians to prescribe warfarin. The prevalence of hypertension in all provinces ranges from 22% to 39.6% Figure 6 .…”
Section: Individual Country Reportsmentioning
confidence: 99%